Livrer à vélo… en attendant mieux - Arthur Jan (La Nouvelle Revue du Travail)
The recent rise of digital platforms linking consumers and self-employed workers has had a strong effect on several economic sectors and raises questions about the working conditions offered by these service providers, plus the kinds of relationships they entertain with activities of this sort. Through a qualitative study of bicycle couriers working for an online food delivery service, the article shows that notwithstanding job insecurity issues, the activity can readily be deemed as something acceptable or even attractive due to the actual content of the work (to wit, the fact that it is cycling-based); its function in the work paths of the individuals involved; and the social resources that they subsequently enjoy. On the other hand, the study also reveals the difficulty of making a long-term commitment to this kind of job as well as the fragility of full-time couriers’ situation.